The Influence of Work Environment and Work Stress on Employee Performance at Maros Salenrang Bakery - S., Nuraliyah; Jusri, Jusri; Rahman, Sundari (Journal of Economics and Management Technologies, 2026)
Objectives – This study aims to determine the effect of the work environment on employee performance at Maros Salenrang Bakery, to determine the effect of work stress on performance at Maros Salenrang Bakery, and to determine the combined effect of the work environment and work stress at Maros Salenrang Bakery. The Methods/Approaches – This study employed a quantitative research approach, which involved collecting data from a specific population or sample, using measurement tools, and conducting quantitative statistical analysis to test hypotheses. The sample consisted of 50 employees from Maros Salenrang Bakery. The Results – The results of the study indicate that, when analyzed individually, the work environment variable has a positive and significant effect on employee performance, with a significance level of 0.001. Meanwhile, the work stress variable does not have a significant effect on employee performance, with a significance level of 0.291. Simultaneously, both variables—work environment and work stress—have a positive and significant effect on employee performance, with a significance value of 0.001, at Maros Salenrang Bakery. Research Implications – This study is expected to serve as a basis for understanding how the work environment and work stress influence employee performance at Maros Salenrang Bakery, as well as a source of information for companies and the general public.